Corrigendum to importance offisheries for food security across threeclimate change vulnerable deltas Science of the total Environment640–641 (2018) 1566–1577 - Lauria, V.; Das, I.; Hazra, S.; Cazcarro, I.; Arto, I.; Kay, S.; Ofori-Danson, P.; Ahmed, M.et.al (Science of the Total Environment, 2018)
On the behalf of my co-authors I submit the following corrigendum: #1 Hilsa kelee should be replaced with Tenualosa ilisha (in 3 places) Appendix A - Table A1 Page 9 - Marine (under common name Hilsa Shad) Page 10 Freshwater (under common name of Hilsa shad) Page 11 Table A2 Freshwater (under common name of Hilsa shad) #2 Penaeus semiculcatus should be Penaeus semisulcatus (in 1 place). Page 10 Table A2 Penaeid Prawn #3 Cirrhinus cirrhosus should be Cirrhinus mrigala (in 3 places). Appendix A Page 10 Table A1 Aquaculture Page 11 Table A2 Freshwater Page 11 Table A2 Aquaculture #4 Oreochromis mossambicus should be Oreochromis niloticus (in 1 place). The fish is not native in Bangladesh, therefore, for tilapia, Oreochromic niloticus – ‘Native’ should be replaced with ‘Introduced’ in 3rd column. (in 1 place). Appendix A Page 10 Table A1 Aquaculture Finally, the acknowledgments of the manuscript should be: This work was funded under the project “Deltas, Vulnerability and Climate Change: Migration and Adaptation (DECCMA)” funded by Canada's International Development Research Centre (IDRC 107642) and the UK's Department for International Development (DFID) through the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA). Jose A. Fernandes received further funding through the Gipuzkoa Talent Fellowships programme, by the Gipuzkoa Provincial Council, Spain. We thank all the people that have helped to collect the data. © 2018 Elsevier B.V.